miR-122 enhances sensitivity of hepatocellular carcinoma to oxaliplatin via inhibiting MDR1 by targeting Wnt/β-catenin pathway - Cao, Fei; Yin, Li-Xue (Experimental and molecular pathology, 2019)
Hepatocellular carcinoma (HCC) is one of the primary causes of cancer-related death and resistance to cytotoxic chemotherapy is the major cause of mortality in HCC patients. miR-122 is a liver specific miRNA and is found to be reduced in HCC, however, the function of miR-122 in HCC chemosensitivity remains elusive. We used qRT-PCR to measure expressions of miR-122, β-catenin and MDR1 in four HCC cell lines. And we assessed the effects of miR-122 or β-catenin on cell viability and apoptosis upon oxaliplatin (OXA) treatment by MTT assay and flow cytometry. In addition, we validated the interactions of miR-122/β-catenin and β-catenin/MDR1 by dual luciferase reporter assay and chromatin immunoprecipitation (ChIP). Western blotting was used to determine the protein levels of β-catenin, Wnt1 and MDR1. In the end, we verified the anti-tumor effect of miR-122 in vivo by using mouse tumor xenograft model. We found that miR-122 was down-regulated in HCC cells. Up-regulation of miR-122 or inhibition of Wnt/β-catenin signaling promoted HCC cells apoptosis and increased the sensitivity of HCC cells to OXA. On the molecular level, we showed that miR-122 directly targeted and suppressed Wnt/β-catenin pathway while β-catenin bound with MDR1 promoter and activated its transcription. Overexpression of miR-122 inhibited MDR1 expression via directly suppressing Wnt/β-catenin pathway. Our study fully demonstrated that miR-122 inhibits MDR1 expression via suppression of Wnt/β-catenin pathway, thereby enhancing HCC sensitivity to OXA. Therefore, miR-122 could serve as a novel potential therapeutic target for HCC. •miR-122 is down-regulated and Wnt/β-catenin pathway is activated in HCC.•Overexpression of miR-122 increases HCC cells' sensitivity to OXA.•Overexpression of miR-122 suppresses Wnt/β-catenin pathway via targeting β-catenin.•β-catenin increases MDR1 expression by binding to the promoter of MDR1.•Overexpression of miR-122 increases OXA anti-tumor effect in vivo.